Berbanine: a new isoquinoline-isoquinolone alkaloid from Berberis vulgaris (Berberidaceae) - Host'álková, Anna; Novák, Zdenek; Pour, Milan; Jirosová, Anna; Opletal, Lubomír; Kunes, Jirí; Cahliková, Lucie (Natural product communications, 2013)
A new isoquinoline-isoquinolone alkaloid was isolated from the root bark of Berberis vulgaris and named berbanine. The structure was established by spectroscopic methods (including 2D NMR, HR-EI-MS).
Keywords: Berberis; Isoquinolines; Alkaloids; isochinoliny; magnetická rezonanční spektroskopie; alkaloidy; kořeny rostlin; Plant Roots; Magnetic Resonance Spectroscopy